Utilizing edible mushrooms as natural flavor enhancers and nutrient sources in meatball products - Putri, Salsabila Hendro; Putranto, Rudi Hendro; Suryatma, Anton; Suryatinah, Yuniarti; Nurlinawati, Iin (Edelweiss Applied Science and Technology, 2025)
Monosodium glutamate (MSG) is widely used as a flavor enhancer in Indonesia; however, excessive consumption has been associated with potential adverse effects on the metabolic, digestive, respiratory, circulatory, and nervous systems. This has prompted interest in developing natural alternatives with comparable flavor-enhancing properties. Edible mushrooms are promising candidates due to their inherent glutamate content and high nutritional value. This study aimed to formulate and evaluate mushroom-based flavorings as natural substitutes for MSG, utilizing three types of edible mushrooms: Pleurotus ostreatus (oyster mushroom), Lentinula edodes (shiitake mushroom), and Auricularia auricula (wood ear mushroom). The mushrooms were dried, ground into powder, and analyzed for their proximate nutritional composition. These powders were processed into flavoring agents and incorporated into beef meatball and sauce formulations. For comparison, three commercial flavorings—Totole (mushroom-based), Halawa (seasoning blend), and MSG—were also tested. A sensory evaluation was conducted using an organoleptic test with 30 panelists to assess attributes such as taste, aroma, and overall acceptability. Among the mushroom-based flavorings, shiitake mushroom performed best, with average scores of 2.90 for meatball sauce and 3.08 for meatballs. However, the commercial flavorings outperformed the natural ones: Totole achieved the highest score for meatball sauce (3.81), and Halawa was most preferred in meatballs (3.90). These results indicate that mushroom-based flavorings, particularly those derived from L. edodes, hold potential as natural flavor enhancers. Nevertheless, commercial products currently offer superior sensory appeal, suggesting a need for further optimization of natural formulations to improve consumer acceptance.